Our numbered bones : a novel - Balen, Katya (HarperVia, 2026)
From an award-winning children's novelist, an adult debut about a grieving author who heads to rural England for a writer's retreat, only to stumble upon an incredible historical find. As the past and present collide, she'll discover the key to healing her trauma.